2013
DOI: 10.3109/0142159x.2013.806791
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging residents to seek feedback

Abstract: Aim: To explore resident and faculty perceptions of the feedback process, especially residents' feedback-seeking activities. Methods: We conducted focus groups of faculty and residents exploring experiences in giving and receiving feedback, feedbackseeking, and suggestions to support feedback-seeking. Using qualitative methods and an iterative process, all authors analyzed the transcribed audiotapes to identify and confirm themes. Results: Emerging themes fit a framework situating resident feedback-seeking as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
98
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(106 citation statements)
references
References 29 publications
4
98
0
4
Order By: Relevance
“…41 We will need to find innovative approaches to encourage continuing education in palliative care and faculty development in teaching palliative care. Steinert et al conducted a systematic review of the literature around faculty development initiatives designed to improve teaching effectiveness.…”
Section: Methods and Scopementioning
confidence: 99%
“…41 We will need to find innovative approaches to encourage continuing education in palliative care and faculty development in teaching palliative care. Steinert et al conducted a systematic review of the literature around faculty development initiatives designed to improve teaching effectiveness.…”
Section: Methods and Scopementioning
confidence: 99%
“…Indeed, Laurillard (2002, 55) argues that "action without feedback is completely unproductive for a learner"; yet it is increasingly apparent that feedback without action is equally unproductive. That is to say, if learning gains are to occur, students must participate actively in the feedback process and act upon the feedback they receive (Delva et al 2013). Relative to the wealth of research on giving feedback, though, researchers note that the education literature has focused considerably less on the process of receiving feedback (e.g., Burke 2009).…”
Section: Introductionmentioning
confidence: 99%
“…19 Delva found that feedback was affected by four factors: learning culture, relationships, purpose of feedback, and emotional responses to feedback. 20 Ende found that feedback was often implicit and inferential rather than explicit, and consequently was frequently misunderstood by residents. 21 Several papers have provided opinions on improving feedback quality.…”
mentioning
confidence: 99%